Petatewalide B, a novel compound from Petasites japonicus with anti-allergic activity. (3rd February 2016) - Choi, Young-Whan; Lee, Kyoung-Pil; Kim, Jung-Min; Kang, Saeromi; Park, Soo-Jin; Lee, Jung-Min; Moon, Hyung Ryong; Jung, Jee H; Lee, Young-Geun; Im, Dong-Soon
Abstract: Ethnopharmacological relevance: The giant butterbur Petasites japonicus is used to treat asthma and allergic diseases in traditional Korean, Japanese, and Chinese medicine. Aim of the study: To elucidate the anti-allergic effect of Petasites genus, we studied effects of several compounds from Petasites japonicus leaves and found a novel bakkenolide-type sesquiterpine. In the present study, anti-allergic and anti-inflammatory effects of the new compound was examined using in vivo and in vitro experiments. Materials and methods: The novel compound was isolated from Petasites japonicus leaves and named petatewalide B. Antigen-induced degranulation and Ca 2+ mobilization were measured in RBL-2H3 mast cells by measuring β-hexosaminidase activity and fluorescence change of Ca 2+ probe, fura-2. Induction of inducible nitric oxide synthase and cyclooxygenase 2 was measured by Western blotting in peritoneal macrophages. In addition, ovalbumin-induced asthma model was used for in vivo efficacy test of petatewalide B. Membrane potential was estimated by measuring fluorescence change of DiBAC in C6 glioma cells. Results: Petatewalide B inhibited the antigen-induced degranulation of β-hexosaminidase in RBL-2H3 mast cells, but did not affect antigen-induced Ca 2+ increase in the cells. Petatewalide B also showed inhibition of the LPS-induced induction of iNOS, but not COX-2 in mouse peritoneal macrophages. Nitric oxide production was also inhibited by petatewalide B in macrophages. In the ovalbumin-induced asthma model, petatewalide B strongly inhibited accumulations of eosinophils, macrophages, and lymphocytes in bronchoalveolar lavage fluid. Petatewalide B increased the membrane potential of C6 glioma cells in a concentration-dependent manner. Conclusion: Petatewalide B from Petasites genus not only has anti-allergic and anti-inflammatory effects but also induces a transient increase of membrane potential in C6 glioma cells. Graphical abstract: